2018
DOI: 10.18632/oncotarget.24822
|View full text |Cite|
|
Sign up to set email alerts
|

Endonuclease G promotes mitochondrial genome cleavage and replication

Abstract: Endonuclease G (EndoG) is a nuclear-encoded endonuclease, mostly localised in mitochondria. In the nucleus EndoG participates in site-specific cleavage during replication stress and genome-wide DNA degradation during apoptosis. However, the impact of EndoG on mitochondrial DNA (mtDNA) metabolism is poorly understood. Here, we investigated whether EndoG is involved in the regulation of mtDNA replication and removal of aberrant copies. We applied the single-cell mitochondrial Transcription and Replication Imagin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
41
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(45 citation statements)
references
References 102 publications
4
41
0
Order By: Relevance
“…5 A). Due to the fact that the METC activity is a major source of ROS and that EndoG regulates mtDNA replication and abundance [ 15 , 28 ], which contains genes codifying for several components of the METC, we checked the expression of several mitochondrial- and nuclear-encoded METC complex subunits in Endog +/+ and Endog −/− fibroblasts and observed no differences ( Fig. 5 B).…”
Section: Resultsmentioning
confidence: 99%
“…5 A). Due to the fact that the METC activity is a major source of ROS and that EndoG regulates mtDNA replication and abundance [ 15 , 28 ], which contains genes codifying for several components of the METC, we checked the expression of several mitochondrial- and nuclear-encoded METC complex subunits in Endog +/+ and Endog −/− fibroblasts and observed no differences ( Fig. 5 B).…”
Section: Resultsmentioning
confidence: 99%
“…ENDOG, the Endonuclease G, was the nuclear encoded gene and its corresponding protein mainly localized in mitochondria. This protein is capable of initiating the mitochondrial DNA replication by generating the RNA primers (51,52). On the one hand, it was the downstream effector of caspase-3 and facilitated the Myc-induced genetic instability and apoptosis (53,54).…”
Section: Discussionmentioning
confidence: 99%
“…Consistently, 8-oxo-dG adducts localize preferentially on fragmented mtDNA upon oxidative stress [202]. High susceptibility of mtDNA to strand breaks and Endonuclease G-mediated degradation was observed upon oxidative stress and proposed as a mechanism for protecting from deleterious accumulation of mutated mitochondrial genomes [203]. Intriguingly, recent works have shown that oxidative stress may also inhibit Endonuclease G activity, thus preventing mtDNA degradation and affecting cell death process [204].…”
Section: Oxidative Signaling In the Mitochondrial Genomementioning
confidence: 99%